Pengaruh Kecerdasan Emosional dan Bias Perilaku terhadap Pengambilan Keputusan Investasi pada Gen-Z di Kota Banda Aceh - Yazma, Azrifa; Anwar, Fathurrahman (Syiah Kuala University Press, 2024)
This study aims to examine the effect of emotional intelligence and behavioral bias on investment decision making on gen-z in the city of Banda Aceh. Data collection in this study was obtained through a google form questionnaire as a data collection instrument for 190 respondents. The sampling technique used in this study is non-probability sampling with the type used purposive sampling. Based on the results of the analysis, it shows that emotional intelligence has a significant effect on investment decision making on gen-z in the city of Banda Aceh and behavioral biases (Overconfidence Bias, Herding Bias, Representative Bias, and Availability Bias) have a significant effect on investment decision making on gen-z in the city of Banda Aceh.Keywords: Investment Decision Making; Emotional Intelligence; Overconfidence Bias; Herding Bias; Representative Bias; and Availability Bias